Trials of Arab Modernity : Literary Affects and the New Political - El-Ariss, Tarek (Book collections on Project MUSE., 2013)
Challenging prevalent conceptualisations of modernity, this study instead offers close readings of the simultaneous performances and contestations of modernity staged in works by authors such as Rifa'a al-Tahtawi, Ahmad Faris al-Shidyaq, Tayeb Salih, Hanan al-Shaykh, Hamdi Abu Golayyel, and Ahmad Alaidy. In dialogue with affect theory, deconstruction, and psychoanalysis, the book reveals these trials to be a violent and on-going confrontation with and within modernity. The author bridges the gap between Nahda (the so-called Arab project of Enlightenment) and postcolonial and postmodern fiction.